SEROLOGICAL STUDY FOR DETECTION OF NEWCASTLE DISEASE VIRUS IN JAPANESE QUAILS IN SOME STATE OF DIYALA PROVINCE, IRAQ - AL-Azawy, Amer KH.; AL-Ajeeli, Karim Sadun (Diyala Agricultural Sciences Journal, 2016)
Newcastle disease (ND) is a highly contagious viral disease all over the world that could cause several losses for the poultry industry. The current study was conducted to clarify the real evidence that the quails play important role in the epidemiology source of NDV. Two groups of quail were used at 50 and150 day old for identification of the NDV. Antigen Rapid Test Kit (Bionote, South Korea) used to identify the positive cases, all positive cases by this kit were tested by Enzyme- Linked Immunosorbent Assay (ELISA) to determine the antibody titers against NDV in all study groups. The results of this study revealed that antibodies against NDV were detected with the mean titer of 2904.39 ±119.238 and 4664.36 ±136.659 to each age groups respectively, in spite of no clinical signs of NDV were observed in thetwo groups. The results referred that quail were carrier for the NDV and may be transmission the pathogen virus to other poultry that housed together, and that calls the attention to the importance of the quail from the epidemiological point of view as a potential source of NDV to commercial poultry (broiler or layer) that housed with or near quails